Enhanced Led Thermal Conductivity Of Filled Epoxy Resin Containing Multimodal Distribution Of Ceramic Particles And Graphene Sheets - Permal, Anithambigai (2018)
Present work was designed to investigate the class of possible materials to be compounded as thermally conductive composite as well as to be catered as thermal interface material (TIM) for an improved thermal performance of a high power light emitting diode (LED) headlamp, a product of OSRAM Opto Semiconductors. This research was earned out to produce a closely packed ceramic and graphene filled hybrid epoxy composite. The work was earned out by understanding the physical and chemical behaviour of aluminium nitride (AIN), boron nitride (BN) and aluminium oxide (AI2O3). Also a comparison of compatibility between two commercial epoxy matrices has been presented in this work. The thermal conductivity of unimodal AIN, bimodal A1N/BN and bimodal AI2O3 were investigated.